Can electric trucks be a viable green logistics and transportation solution? Modeling a joint logistics-and-charging-infrastructure network design problem - Yu, Hao; Adhikari, Amit; Sun, Xu; Solvang, Wei Deng; Gan, Mi; Aydin, Nezir (ELSEVIER, 2026)
As one of the most substantial contributors to the rapidly increasing carbon emissions, the greening and decarbonization of the transportation and logistics sectors are essential. In this context, electric trucks (E-trucks) have garnered global interest due to their potential to significantly reduce tailpipe emissions in the freight transport sector. However, inadequate charging infrastructure is a substantial barrier to the widespread adoption of Etrucks. This paper investigates a charging infrastructure development model led by an industry cluster in order to better meet the emission target. To this end, a new optimization model is formulated for a joint logistics-and-charging-infrastructure network design problem. The model aims to minimize the total cost of operating the logistics system and charging infrastructure network while simultaneously ensuring accessibility to charging stations. Numerical experiments based on a case study in Nepal were conducted to validate the proposed optimization model. The results demonstrate potential reductions of up to 33.3% in total logistics costs and 55.9% in emissions related to transportation through the transition to electric power. This analysis highlights the economic viability and environmental benefits of adopting E-trucks in green logistics and transportation, supported by an industry-spearheaded business model for developing charging infrastructure.
Keywords: Green logistics; Electric trucks; Network design; Charging station; Infrastructure development; Optimization; LOCATION PROBLEM; VEHICLES; Transportation